Komposit hampas sagu dalam pembuatan panel penyerap bunyi - Noorhaizat, Bin Sundin (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The purpose of this research is to update the application of the origin material which is sago waste and to develop "Sound Ansorber Panels". The physical characteristic of sago waste is consist of small paticles and soft fiber in yellow colour. It is the outcome from deposits moist in much amount during the starch extraction process. Sago waste properties have their strength, weaknesses and uniqueness of their own. In this research, composite process is applied with various binders and polymers. This product has utilizes the sago waste into a high value added product, that is potentially commercial in the high market of music industries globally. In order to achieve the specific objectives, the function and basic manufacturing of sound absorbers products must be aligned with the present products in the market.